The different roles of a cationic gold(i) complex in catalysing hydroarylation of alkynes and alkenes with a heterocycle. Issue 60 (5th July 2016) - Mehrabi, Tahmineh; Ariafard, Alireza
Abstract : Hydroarylation of alkenes is promoted by a proton released by interaction of a cationic gold complex with an acidic species. Abstract : The mechanism of twofold hydroarylation of terminal alkynes with pyrrole catalyzed by a cationic gold(i ) complex was investigated using DFT. It was found that while both the hydroarylation reactions proceed via a Friedel–Crafts-type mechanism, the first hydroarylation is directly promoted by gold(i ) but the second hydroarylation by a proton released through interaction of the alkene product with gold-bound acidic organic species such as acetic acid and terminal alkynes.